EVALUASI KENDALA DAN MASALAH IMPLEMENTASI UU 22/2009 TENTANG LLAJ TERHADAP CAPAIAN PENYELENGGARAAN JALAN NASIONAL - Taufik Mulyono, Agus; Abu Sandra, Putra (Jurnal Transportasi, 2013)
The Law No. 22/2009 on Road Traffic and Transportation dictates the national road authorities to perform proactively, reactively, and with fullest anticipation with regards to the safety aspects in administering road provision. In relation to this demand, data collection was conducted in Provinces of Riau, East Java, South Kalimantan, South Sulawesi, and East Nusa Tenggara through a series of focussed discusions involving road authorities, road traffic and transportation regulators, as well as law enforcement officers. Proactive measures that still fell short to meet the demand were related to Article 8 (stipulation of roadâs level of service, optimized utilization of road segments, geometric betterment of roads and intersections, stipulation of road classes, and attainment of road worthiness). Reactive measures that still lag in enforcement were related to Article 24 (improvement of road sections with safety deficiencies, and installation of road signs at damaged road sections or roads with substandard geometric to prevent accidents). Anticipative measures in need of attention were related to Article 230 (road unworthiness as a contributing factor to cause accidents), and Article 273 (poor road conditions that might cause accidents, and in consequence of which, road authorities could face 5 year imprisonment in cases invloving fatalities).Keywords: proactive, reactive, action, road